Neuroprotective Properties of Wild Mango (Mangifera caloneura Kurz) Leaves on Alleviating Urban Air Pollutant Toxicity: Insights From Transcriptome Analysis of a Human Neuronal Cell Model - Parinee Kittimongkolsuk; Suporn Sukjamnong; Sakawrat Janpaijit; Panthakarn Rangsinth; Sawarin Chumpolphant; Kamonwan Chaikhong; George Pak‐Heng Leung; Valerie W. Hu; Tewarit Sarachana; Anchalee Prasansuklab; Tewin Tencomnao (Food Frontiers)
ABSTRACT Exposure to urban air pollution, particularly particulate matter (PM), has been correlated with an increased risk of neurodegenerative diseases, notably Alzheimer's and Parkinson's diseases. However, the mechanisms underlying the association between urban air pollution and neurodegenerative diseases remain unclear. In this study, we investigated the toxic effects and underlying mechanisms of urban dust on SH‐SY5Y cells using high‐throughput transcriptomic sequencing. In addition, we explored the neuroprotective potential of an ethanol extract of wild mango (Mangifera caloneura) leaves (MCE) against urban dust‐induced neurotoxicity. Our results demonstrated that urban dust significantly induced intracellular reactive oxygen species generation, reduced nuclear factor erythroid 2‐related factor 2 (Nrf2) activation, and decreased both mitochondrial membrane potential and adenosine triphosphate production. Transcriptomic analysis revealed altered expression of several genes associated with oxidative stress and neurodegenerative diseases, compared to control cells. Notably, co‐treatment with MCE reversed the detrimental effects caused by urban dust, particularly by enhancing Nrf2 nuclear translocation, increasing sirtuin 1 and superoxide dismutase 1 levels, and normalizing the altered gene expression patterns. In summary, MCE shows potential as an alternative therapeutic agent for preventing oxidative stress associated with air pollution‐induced neurodegenerative diseases.